Architect Ivo Radić: Merging International and Regional Design Principles in Collective Housing in the 1960s in Split, Croatia - Vesna Perković Jović; Neda Mrinjek Kliska; Ivan Mlinar (Heritage)
Ivo Radić (Split, 1930–Split, 2006) is a prominent Croatian architect who contributed mostly to the field of residential architecture and tourism facilities. The most important buildings that he designed were realised in Split, a city in the Mediterranean part of Croatia. Buildings that he designed have many features of the International style. Nevertheless, in their design, the architect also successfully introduced the elements of regional Mediterranean vocabulary, using contemporary materials and technology. This paper is focused on three formative projects of architect Ivo Radić, analysing them by their urban context, architectural design and technical innovation of their architectural elements, trying to outline the architect’s discourse. The aim of the research is to emphasise the importance of Ivo Radić’s work in the context of the modernist urban and architectural heritage of Split and Croatia and to underline the need to define an appropriate approach in the evaluation and protection of the heritage of modernist residential architecture and urbanism.